Design And Construction Of Cabinet Dryer With Variation Of Blower Speed Using Charcoal Combustion On Chilli Plants - Muhammad Rosyidi; Arasy Fahruddin (Universitas Muhammadiyah Sidoarjo, 2022)
Indonesia is one of the tropical countries where there are many entrepreneurs engaged in chili farming found in rural areas. Chili is a commodity plant that is in great demand throughout the world and in Indonesia, therefore without good processing or preservation, the quality of chili quickly rots and the price drops in the market. In the chili processing process, it is very dependent on sunlight, but due to the uncertain climate and drying using sunlight, it needs a long and unhygienic process, causing the chili processing process to be hampered. For this reason, the design of a drying system that utilizes heat from burning charcoal is specifically designed to speed up the drying process. This chili drying system utilizes heat from burning charcoal in the furnace and flows hot air into the system with the help of a blower whose speed is varied, namely 6000 Rpm, 4000 Rpm and 2000 Rpm, with variations in the testing capacity scale to determine the tamping power on an efficient rack when this dryer works. After testing the tool, it is known that in a drying time of 30 minutes, the variation is more effective with an even distribution of heat in the system with a maximum blower speed of 100 grams with a drying rate of 20% to 30%.